2017
DOI: 10.1108/mrr-10-2014-0233
|View full text |Cite
|
Sign up to set email alerts
|

Enabling factors that contribute to women reaching leadership positions in business organizations

Abstract: Structured abstractPurpose: While the number of women working in management accounting has increased, the percentage of female executives in this area remains low. Previous studies examining the underrepresentation of women in accounting leadership positions have analyzed factors that hinder women from reaching these positions. The aim of this paper, by contrast, is to identify factors that support the advancement of those female executives who have reached a leadership position. Further, this paper highlights… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 86 publications
0
22
0
Order By: Relevance
“…Personal competency is related to self-evaluation, attitude to work, motivation, ambition and other aspects (Raudeliūnienė and Neimontas, 2012). Furthermore, Cimirotić et al (2017) emphasize the importance of ambition and the ability to defend personal opinion (Cimirotić, Duller, Feldbauer-Durstmüller, Gärtner, & Hiebl, 2017). Ambitious women leaders are able to identify possibilities even in risky situations and use it to prove their abilities (Hurley & Choudhary, 2016), although capabilities of identifying and assuming risks are assigned as masculine traits of leadership (Acar, 2015;Dambrin & Lamber, 2008;Evans, 2014).…”
Section: Literature Reviewmentioning
confidence: 99%
See 4 more Smart Citations
“…Personal competency is related to self-evaluation, attitude to work, motivation, ambition and other aspects (Raudeliūnienė and Neimontas, 2012). Furthermore, Cimirotić et al (2017) emphasize the importance of ambition and the ability to defend personal opinion (Cimirotić, Duller, Feldbauer-Durstmüller, Gärtner, & Hiebl, 2017). Ambitious women leaders are able to identify possibilities even in risky situations and use it to prove their abilities (Hurley & Choudhary, 2016), although capabilities of identifying and assuming risks are assigned as masculine traits of leadership (Acar, 2015;Dambrin & Lamber, 2008;Evans, 2014).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Smith et al (2010) carried out the study in the countries of North Europe and found out that the time spent bringing up children had a direct impact to the pay gap and decrease women's possibilities to reach executive positions in companies (White & Smith, 2010). Therefore, the mobility of a workplace (Subramaniam et al, 2013) and flexible working hours (Cimirotić et al, 2017;Hurley & Choudhary, 2016) give possibilities to women leaders to balance their work and private life. Due to the fact that women usually face more obstacles than men in leader positions, the support of external environment is identified as an extremely significant factor of successful women's leadership.…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations